Trajan's hollow - Stein, Joshua G. 1972- (ORO Editions, 2019)
This publication documents 'Trajan's Hollow', a transformative reproduction of Trajan's Column in Rome, to address issues of critical importance in contemporary architectural practice: a reconsideration of architectural poch (both programmatic and material), the use of scale shift as a tool for transforming shape and content, and the role of subversive reconstruction in an era of digital scanning and replication. The publication offers an alternative model for the close reading of historical artifacts through an analysis of Trajan's Column and its material progeny, including the casts and copies of the column produced over 2,000 years and contemporary reconstructions of the column executed by the author while in residence at the American Academy in Rome. Although this second-century monument located in the heart of Rome has been the object of hundreds of years of study, 'Trajan's Hollow' uncovers aspects of the column curiously omitted amidst all this attention, manifesting the lacunae in various paradigms of historical inquiry: this work rereads the column and its legacy through the simple act of prioritizing the embodied occupation of its interior over the analysis of its exterior narrative frieze
Includes index. - Published by Applied Research and Design Publishing. An Imprint of ORO Editions
Keywords: Trajanssäule -- Rom; Trajan's Column (Rome, Italy); Columns / Rome; Architecture, Roman; Rome (Italy) / Antiquities; Rome (Italy) / Buildings, structures, etc; Antiquities; Buildings; Columns; Italy / Rome; Rome (Empire); Bildband